2022
DOI: 10.1007/s11740-022-01126-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the friction conditions of self-pierce rivets by means of a compression-torsion tribometer

Abstract: Lightweight design is an effective lever for achieving fuel consumption and emission-oriented goals. Therefore micro-alloyed steels and high-strength aluminium materials are included in the multi-material mix of the car body. In this context self-pierce riveting has become established for joining in body-in-white production. For the dimensioning of the joint, numerical simulation is increasingly being used. In order to make reliable predictions about joint quality, knowledge of the friction in the joining proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was found that friction coefficients between the die and bottom sheet and between the rivet and top sheet had the most significant influences on the joint quality. Suitable friction coefficients for the studied SPR To overcome the disadvantages of the experimental approach, numerical analyses with a finite element (FE) model have also been conducted in some studies to explore the impact of surface conditions [15,16]. It has been widely proved that a properly calibrated FE model of the SPR process can accurately predict the riveting force [17], material deformation behaviour [18] and final joint quality [19].…”
Section: Clampingmentioning
confidence: 99%
“…It was found that friction coefficients between the die and bottom sheet and between the rivet and top sheet had the most significant influences on the joint quality. Suitable friction coefficients for the studied SPR To overcome the disadvantages of the experimental approach, numerical analyses with a finite element (FE) model have also been conducted in some studies to explore the impact of surface conditions [15,16]. It has been widely proved that a properly calibrated FE model of the SPR process can accurately predict the riveting force [17], material deformation behaviour [18] and final joint quality [19].…”
Section: Clampingmentioning
confidence: 99%